EMOTIONAL INTELLIGENCE AND ITS PSYCHOLOGICAL SIGNIFICANCE - Abdakimova Mamlakat Abdusamad qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Emotional intelligence (EI) refers to the ability to perceive, understand, manage, and regulate emotions in oneself and others. This paper explores the psychological importance of emotional intelligence in personal development, mental health, interpersonal relationships, and academic and professional success. Through a review of key theories and recent research findings, the paper outlines how EI supports emotional stability, decision-making, stress management, and social adaptation.